An investigation into Mara University of Technology Samarahan and Mukah campus pre-commerce students’ perspectives on second language learning / Caesar Dealwis , Baljinder Singh Maghar Singh & Sueb Ibrahim - Dealwis, Caesar; Maghar Singh, Baljinder Singh; Ibrahim, Sueb (2005)
This is an exploratory study which aims to investigate learners’ perceptions of language learning in two UiTM campuses in the state of Sarawak. The researchers were guided by the research question — What are the ideas of UiTM students on language learning in terms of the following aspects: the usefulness of various language learning activities; the nature of language learning; the ideal language learning situation; and how they learn English. The study also aimed to find out if there are differences in students' perceptions, in particular between male and female, and those in Mukah and Samarahan campuses respectively.